Between Apathy and Antipathy: The Vikings in Irish and Scandinavian History - HOLM, POUL (My University, 1995)
"Neither apathy nor antipathy can ever bring out the truth of history" (Eoin MacNeill, Phases of Irish History, Dublin, 1919, vi). Around 1970 the subject of "the Vikings in Ireland" was seen, historiographically, as a non-problem. Scandinavian historians did not deal with Irish history, and except for the casual asides of four or five specialists, there was no particular interest in Ireland as an area in Viking studies. However, during the seventies there was a veritable boom in specialised studies of the Vikings in Ireland. A simple count reveals that during this decade sixty articles and some books of scholarly significance were published, whilst the average formerly never exceeded twenty publications a decade. This growth took place even before the fruits of the Viking excavations in Dublin had matured for publication, something that happened only in the eighties. Of course, the validity of scholarly debate is not to be judged simply on the basis of a spate of small treatises. A specialised subject can only claim general interest if its historians ? basing themselves on empirical knowledge ? lead a debate on issues of central historical interest. Motives scholarly as well as institutional, political as well as cultural, lie behind the various interpretations which make every (or every second) generation write its history. In this article I aim to show how the subject of the Vikings in Ireland eminently displays these characteristics, and at the same time I hope to point to some historiographical reasons why the subject failed to inspire historians around the middle of the twentieth century. There is no considered overview of the historical debate at hand, excepting a short and very negative review by the Norwegian Per Sveaas Andersen.1 Several interesting comments were made in 1968 by Francis John Byrne in a review of thirty years' work in early medieval Irish history, and by Donnchadh O Corrain in his hand list of publications on early Irish history.2 Michael Chesnutt and Bo Almqvist have written good presentations of the relations between Irish and Icelandic literature and folk-lore3 but these matters will not be dealt with here. First, I want to investigate the early formulation of the basic questions regarding the Viking contribution to Irish history.
PUBLISHED
Keywords: Viking; historiography; Cogadh; Medieval Ireland